Education for Resilience : Exploring the Experience of Refugee Students in Three Communities in Ethiopia - World Bank Group (World Bank, Washington, DC, 2019)
The objective of this report is to support evidence-based decision making for refugee education in Ethiopia. This study was designed to inform existing and pipeline projects of the Government of Ethiopia, the World Bank, and key development partners, and to provide help with long-term engagement of the World Bank on education in Ethiopia. The research questions for this study, hence, emerge from the knowledge gaps identified by the project teams and other relevant development partners. Qualitative data was gathered from sample refugee populations in three areas of Ethiopia: Gambella region, Somali region, and Addis Ababa. Participants included refugee parents and children, and teachers serving refugee students in refugee schools as well as host community schools. Key findings of the current qualitative study are summarized in this report, followed by broad areas of recommendations.